Hiszpańskie korzenie rodu Teodozjusza w poezji Klaudiana - Babnis, Tomasz (Collectanea Philologica, 2024)
Theodosius the Great was one of the great Romans of Iberian origin. The poetry of Claudian, the court poet of his son, Honorius, is full of praise for the Theodosian dynasty, hence one can find there also references to Spain as the cradle of the ruling house. The poet praised not only the emperors, but also referred to other members of the dynasty, in particular to Serena, Theodosius’ adoptive daughter and Stilicho’s wife. The commendation of the honorand’s country of origin was an important part of ancient panegyrics and Claudian mentioned Spain several times in this context. Such references are rather vague and general, frequently touching the aquatic environment an only once, in Laus Serenae, make up a longer passage belonging to the subgenre of laudes. The poet underlined also the relation (suggesting the fictive genealogy) between the Theodosian dynasty and the earlier emperors of Iberian origin, i.e. Trajan and Hadrian. By dint of the aforementioned passages Claudian tried to strengthen the position of Theodosians, to date known rather from their activities in the East, and to emphasize their connections with the Western Empire.